Design and Construction of the Control System for Batan Small Angle Neutron Scattering Spectrometer (SMARter) - E. Santoso; E.G.R. Putra (PPIKSN-BATAN, 2008)
A 36 m Small Angle Neutron Scattering (SANS) Spectrometer (SMARTer) has been installed in Serpong, Indonesia in 1992. As time goes by, the original main computer was out of order and the instrument had not been operated since 2003. In order to activate the SMARTer, in the year 2005, a work on designing and constructing a new control system for SMARTer was carried out. The main component of this control system is a programmable peripheral I/O (IC PPI 8255) and was assembled as a plug-in board at an ISA slot of a personal computer. An IC PPI 8255 was programmed to control the mechanical movements of the instrument’s components: four neutron guide tubes, six pinholes collimator, a detector and a beam stopper. The test either with or without neutron beam has shown that this control system can be implemented for the mechanical movements of SMARTer. Error of moving the detector in the distance range of 1.5 m – 18 m is only 1 mm and the other movements have no error at all (precise).